On the transverse vibration of beam under the action of some moving body - Nguyen Van Khang; Do Xuan Tho (Vietnam Journal of Mechanics)
In this work the structure method is applied for establishing the vibration equations of beam under the action of some moving body. An algorithm is build to solve the vibration equations of the considerable system. From this algorithm a computer program is set up with TURBO PASCAL 6.0 language.